The Retina Illustrated - Ehlers, Justis P. (Thieme Medical Publishers, Incorporated, 2019)
A day-to-day guide on the diagnosis and management of routine to complex retinal disorders The diagnosis and treatment of retinal eye disorders often presents significant clinical challenges. The Retina Illustrated, edited by renowned retina specialist Justis Ehlers and an impressive group of worldwide contributors, provides a rapid-fire yet thorough approach to the visual world of retinal disease. Organized into ten sections and 102 succinct yet comprehensive chapters, this richly illustrated reference covers the full spectrum of retinal disorders, ranging from common degenerative diseases to.